There Is a Method to the Madness: Strategies to Study Host Complement Evasion by Lyme Disease and Relapsing Fever Spirochetes - Marcinkiewicz, Ashley L.; Kraiczy, Peter; Lin, Yi-Pin (Frontiers in Microbiology, 2017)
Lyme disease and relapsing fever are caused by various Borrelia species. Lyme disease borreliae, the most common vector-borne pathogens in both the U.S. and Europe, are transmitted by Ixodes ticks and disseminate from the site of tick bites to tissues leading to erythema migrans skin rash, arthritis, carditis, and neuroborreliosis. Relapsing fever borreliae, carried by ticks and lice, trigger reoccurring fever episodes. Following transmission, spirochetes survive in the blood to induce bacteremia at the early stages of infection, which is thought to promote evasion of the host complement system. The complement system acts as an important innate immune defense mechanism in humans and vertebrates. Upon activation, the cleaved complement components form complexes on the pathogen surface to eventually promote bacteriolysis. The complement system is negatively modulated by a number of functionally diverse regulators to avoid tissue damage. To evade and inhibit the complement system, spirochetes are capable of binding complement components and regulators. Complement inhibition results in bacterial survival in serum (serum resistance) and is thought to promote bloodstream survival, which facilitates spirochete dissemination and disease manifestations. In this review, we discuss current methodologies to elucidate the mechanisms of Borrelia spp. that promote serum resistance and bloodstream survival, as well as novel methods to study factors responsible for bloodstream survival of Lyme disease borreliae that can be applied to relapsing fever borreliae. Understanding the mechanisms these pathogens utilize to evade the complement system will ultimately aid in the development of novel therapeutic strategies and disease prevention to improve human health.